Conflicts and alternative mechanisms in displaced communities from Quibdó (Chocó-Colombia) - Cuesta Cuesta, Doris (DIXI, 2013)
We aimed to ref lect, by means of surveys and interviews, both the conf licts of, and the mechanisms employedby, the displaced communities of Quibdó, as well as their socioeconomic characterization. The results allowus to propose alternative mechanisms for conf lict resolution that may foster a peaceful cohabitation in thisdepressed zone of the country.
Keywords: Chocó; conflicts; displaced population; mechanisms; solution